(untitled) (Journal of Surgical Sciences, 2019)
Despite significant improvement in the management strategy, pancreatic cancer continues to be a great challenge for surgeons and oncologists. Length of survival largely depends upon stage at diagnosis and a completeness of resection. Distal pancreatectomy with RO resection has been reported as a favorable method in selected pancreatic body and tail tumors. Additional organ resections are rarely required. A young woman was diagnosed with a tumor in the body and tail of the pancreas that required splenectomy in addition to dista1 pancreatectomy. Postoperative course was uneventful. Histopathology revealed the tumor as moderately differentiated adenocarcinoma with extensive areas of necrosis, haemorrhage and cholesterol cleft formation. Resected end of pancreas was free of tumor. She has completed a course of chemotherapy and is doing well after 8 months of surgery. Journal of Surgical Sciences (2014) Vol. 18 (2) : 78-82